Response of GHG emissions to interactions of temperature and drying in the karst wetland of the Yunnan-Guizhou Plateau - He, Yan; Zhang, Tao; Zhao, Qiumei; Gao, Xiaoye; He, Tengbing; Yang, Shimei (Frontiers in Environmental Science, 2022)
Hydrothermal fluctuation is the major driving factor affecting greenhouse gas (GHG) emissions in wetlands, but how wetland drying regulates the temperature dependence of GHG emissions remains uncertain. An experimental incubation was carried out to study the interaction effects of temperature (5, 10, 15, 20 °C) and moisture (40%, 60%, 100% WHC) on soil GHG emissions in a karst wetland. The results showed that the cumulative CO2 and N2O emissions and global warming potential (GWP) increased with increasing temperature but decreased with soil drying. There was a decreasing contribution of CO2 and an increasing contribution of N2O to GWP with increasing temperature and moisture. Temperature and soil drying positively interacted with CO2 and N2O emissions and GWP. Soil CO2 and N2O emissions and GWP were positively related to urease activity and negatively related to pH, soil organic matter and catalase. Soil CH4 emissions were positively related to soil microbial biomass C and N. The hydrothermal changes, soil properties and their interaction explained 26.86%, 9.46% and 49.61% of the variation in GWP. Our results indicate that hydrothermal fluctuation has a significant effect on total GHG emissions by regulating soil properties, and the contribution of CO2 emissions to GWP will decrease under climate warming but increase under wetland drying conditions due to changes in N2O emissions.